Gender and Politics: Gender Balance as a Panacea to a Credible and Successful Election - Obinna Ogbonna, Hyginus; Mbah, Chidi Slessor; Imoudu, Monica O. (Richtmann Publishing, 2021)
This paper focuses on Gender Balance as a Panacea to a Credible and Successful Election, having as its raison dâ€™Ãªtre: to review the concept of gender balance and appropriate its implications towards achieving a credible and successful election required for the existence of human centered development process in sub-Saharan Africa, with Nigeria as a case study. Thus, the paper achieves its goal by adopting a qualitative descriptive method of analysis as it examines qualitatively: the urgency for the crusade on gender balance; the inter-linkages between gender balance and a credible-successful election. A few theoretical orientations were employed to mediate for a proper epistemic extrapolations and reconstructions to explaining gender balance as a panacea to a credible and successful election: these include, the notion of Social Contract, the notion of Democratic Culture, and the notion of Participatory Electoral Process. The paper made some findings, a few of these include: 1) there is the tendency in the sub-Saharan African socio-political cultural practice, Nigeria in particular, to socially exclude women in politics because the female gender has been judged first of all from sexuality point of view as a second class gender rather than seeing women, first of all, as humans, hence entitled to human rights for which right to political participation is inclusive. 2) There is a correlation between gender balance and a credible-successful election, and the absence of the former reproduces a negative outcome in the latter. The paper therefore concludes that strict observance of gender balance is a sine qua non for a credible-successful election conducive for human centered development process. It thus recommends for the total commitment of government to democratic culture by mainstreaming women in politics, inter alia. Received: 27 July 2021 / Accepted: 15 October 2021 / Published: 5 November 2021